About a new type of redeposition of fossils - K. I. Yushin; V. N. Komarov (Известия высших учебных заведений: Геология и разведка, 2017)
At the final stage of the taphonomic cycle, after the deposit has gone to the surface in a result of different processes, the alteration of the deposit in the zone of surface weathering occurs, due to the mechanic destruction as well as the processes of soiution and replacement. A phenomenon of the deposition in thanatocenosis the reburied fossils - redeposition - has a widespread occurrence in this time. On the basis of the unique finding of the cervical vertebra of the Upper Pleistocene European roe deer in the modern freshwater catfish (Silurus glanis Linnaeus) a new type of the fossils redeposition - biogenic, which can be realized by a variety of the organisms. Its account can be used for a more complete breakdown of the processes, which lead to the forming of the deposits.